The Use of Self-Created Podcasts to Enhance German Speaking Proficiency - Melky Ayu Wijayanti; Genita Cansrina; Nada Muthia Zahrah; Farhana Muslim Mohd Jalis (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2025)
T This study focuses on podcasts as a medium for enhancing speaking competence in German as a Foreign Language (DaF) instruction. In contrast to existing research, this study emphasizes student-created podcasts and their didactic potential in higher education contexts. The key research questions explore how podcasts can be integrated into the classroom, how project-based learning through podcasts supports language acquisition, and how their use affects speaking proficiency. The study is conducted with German language students at UNJ and UNPAD at the B2 proficiency level. Initial survey results indicate that the use of podcasts increases students' motivation to learn German. Furthermore, findings suggest that creating their own podcasts not only improves students' linguistic abilities but also fosters 21st-century skills, including learning and innovation competencies as well as media, information, and technology literacy—skills that align with Indonesia’s educational goals.  The study's findings aim to provide German language instructors with further insights and practical ideas on how podcasts can be effectively implemented in DaF instruction to better meet the needs of today's learners.